The Application Of Big Data And Artificial Intelligence In Business Decision-Making Based On Infocom Technology - Akhiyar, Dinul; Nofriadiman (Riset Sinergi Indonesia (RISINDO), 2024)
The rapid development of Information and Communication Technology (Infocom) has led to significant advancements in business decision-making, particularly through the application of Big Data and Artificial Intelligence (AI). This paper explores how these technologies are utilized to enhance business decision-making processes, providing organizations with valuable insights and predictive capabilities. Big Data refers to the vast amount of structured and unstructured data generated from various business activities, while AI leverages algorithms and machine learning techniques to analyze this data, uncover patterns, and make informed predictions. The integration of Big Data and AI enables businesses to improve efficiency, optimize resource allocation, and gain a competitive edge in a dynamic market environment. The paper discusses various applications, including predictive analytics, customer segmentation, and supply chain optimization, highlighting their impact on strategic and operational decision-making. Moreover, it addresses the challenges associated with the implementation of these technologies, such as data quality, privacy concerns, and the need for skilled professionals. Ultimately, the study emphasizes that the synergy between Big Data and AI, when effectively implemented, can drive data-driven business strategies and foster innovation.